Eklezjalne cele „Pierwszej mowy o pokoju” Grzegorza z Nazjanzu - Widok, Norbert (Vox Patrum, 2020)
Of the three orations on peace, the first one was delivered by Gregory of Nazianzus most probably in February 364. Its leading theme was the restoration of peace and consensus among the disputing parties in the Nazianzus church community. The reason for the dispute turned out to be the Gregory the Elder’s wrong signature made under the profession of faith, which was disseminated by an Arian representative in this place. For the narrator, the basis for restoring peace was to spread ideas that would join the warring parties, i.e., faith in one God, consistent interpretations of Trinitarian issues and desire for unity. The peace sought by Gregory turned out to be a value unifying all those who formed the church community of Nazianzus and at the same time a dimension introducing unanimity in matters of faith. Thanks to the theological elucidations provided by the young priest at the time, the ecclesial unity and mutual peaceful relations in Nazianzus could be restored.